PENGARUH SERAT CACAHAN LIMBAH PLASTIK POLYETHYLENE TEREPHTHALATE TERHADAP KUAT TARIK BETON UNTUK BANGUNAN - ., HASRIANA; ., EFRAIM (FORUM BANGUNAN, 2012)
The research was conducted on the basis of the increase in flexural tensile strength of concrete and waste utilization polyethylene Terephthalate (PET). The purpose of this study was to determine the influence of type of Polyethylene Terephthalate fiber plastic ( PET ) to slump value , volume weight and flexural tensile strength of concrete with high levels of variation of 0.0 % , 0.1 % , 0.3 % and 0.5 % . Specimens used for robust experimental dance, using a beam with a 10 cm high, 10cm wide and 40 cm long. The procedure was performed starting from the preparation of materials , inspection / testing of materials , the concrete mix design , manufacture specimen , specimen maintenance and testing of flexural tensile strength of concrete .The results of the study as follows : BN = 5.37 MPa , B. PET 0.1 % = 5.89 MPa , B. PET 0.3 % = 6.47 MPa , and B. PET 0.5 % = 6.86 MPa . Thus flexural tensile strength test results of concrete can be concluded, the more the percentage of fiber additions on each specimen, the value of the flexural tensile strength of concrete is the better. Proven flexural tensile strength of concrete testing was done with the addition of PET 0.1 %, 0.3 % and 0.5 %.